Selenium-enriched Bifidobacterium longum DD98 effectively ameliorates dextran sulfate sodium-induced ulcerative colitis in mice - Hu, Yongjia; Jin, Xueli; Gao, Fei; Lin, Ting; Zhu, Hui; Hou, Xiao; Yin, Yu; Kan, Shidong; Chen, Daijie (Frontiers in Microbiology, 2022)
The pathogenesis of ulcerative colitis (UC) is complicated with impaired intestinal epithelial barrier and imbalanced gut microbiota. Both selenium and probiotics have shown effects in regulating intestinal flora and ameliorating UC. The objective of this study is to investigate the alleviating effects of Selenium-enriched Bifidobacterium longum DD98 (Se-B. longum DD98) on dextran sulfate sodium (DSS)-induced colitis in mice and explore the underlying mechanism. After treatment of B. longum DD98, Se-B. longum DD98, and sulfasalazine for 3 weeks, the disease severity of UC mice was decreased, with colon lengthened and pathological phenotype improved. The expression of pro-inflammatory cytokines and oxidative stress parameters were also decreased. Thus, Se-B. longum DD98 showed a stronger effect on relieving the aforementioned symptoms caused by DSS-induced colitis. Exploration of the potential mechanism demonstrated that Se-B. longum DD98 showed higher activities to suppress the inflammatory response by inhibiting the activation of the toll-like receptor 4 (TLR4), compared to B. longum DD98 and sulfasalazine. Se-B. longum DD98 also significantly improved the intestinal barrier integrity by increasing the expression of tight junction proteins including ZO-1 and occludin. 16S rDNA sequencing analyses showed that Se-B. longum DD98 improved the diversity of the intestinal flora and promoted the abundance of health-benefiting taxa including Lachnospiraceae, Lactobacillaceae, and Prevotellaceae in family level. In conclusion, compared to B. longum DD98 and sulfasalazine, Se-B. longum DD98 showed stronger therapeutic effects on DSS-induced colitis in mice and might be a promising candidate for the treatment of UC.